Solid-state microwave induced plasma synthesis of antimony telluride - Suriwong T. (2014)
The utility of microwave heating and microwave generating of plasma as a synthetic technique toward the synthesis of Sb2Te3 is reported. The solid-state microwave synthetic method was studied the effects of irradiation times and cycles, and molar ratio of Sb:Te at a 900 W irradiated microwave power in order to determine phase purity of the reaction products. X-ray powder diffraction, field-emission scanning and transmission electron microscopic, including Raman spectroscopic techniques were used to investigate their phase, structures, surface morphologies and vibration characteristics. Their optical properties were also investigated by UV-vis and luminescent spectrophotometries. ©2010 IEEE.